'Being young and LGBT, what could be worse?' Analysis of youth LGBT activism in Indonesia: challenges and ways forward. Issue 1 (2nd January 2018) - Ridwan, Rinaldi; Wu, Joyce
ABSTRACT: Young Indonesian LGBT people are currently mobilising against a wave of conservatism and violence in an increasingly anti-LGBT context. Young LGBT people are showing remarkable courage and strategic thinking and mobilising in a range of ways. These include grassroot peer support, advocacy, and partnerships with government, adult-led non-government organisations and the private sector. However, these youth also face multiple challenges. This article highlights findings from a 2016 study of mobilisation by youth LGBT activists, using in-depth feminist qualitative research methods. The aim of the research was to highlight the resilience of young LGBT people in Indonesia, the barriers they face, and to consider what feminists and development policymakers and practitioners can do to support them.